Resistance training for metabolic syndrome: Part I - Sorace, P.; Ronai, P.; Churilla, J. R. (Strength and Conditioning Journal, 2013)
This column will focus on discussing the components of metabolic syndrome (mets) and the benefits resistance training (RT) may have on these components and the mets as a whole.